Regulation of the "too-big-to-fail" entities in the Republic of Croatia - Rubinić, Ivan (Array, 2018)
The contemporary stand among scientists is that the role of the state, within mixed market economies, should be reduced to the task of ensuring the institutional framework in order to protect the free market. However, occurrences of the “too-big-to-fail” entities constitute a challenge for the government regarding its ability to manage economic affairs in the traditional manner. Given that the nature of these entities makes them relevant on the verge of their own collapse, the authors focused on the legal and economic aftermath of their failures. The authors undertook extensive research into this topic with the primary goal of arguing that government regulation, in the cases of collapsing “too-big-to-fail” entities, is necessary for achieving stability of the system. After researching of the government’s role both in theory and practice, the authors displayed the findings of the analysis of the legal possibilities within the bankruptcy law of the Republic of Croatia. The historical and practical context of the research is the implementation of the legislation in the complex case of Agrokor Group. Ultimately, the authors argue that the magnitude of the collapsing “too-big-to-fail” company requires government intervention in order to preserve economic stability in the region, in addition to maximizing social welfare.